PERAN TANDA TERIMA SEBAGAI ALAT PENGENDALIAN INTERNAL DALAM PROSES ADMINISTRASI KEUANGAN PT SWABINA GATRA - Putri, Azzahra Setya; Takarini, Nurjanti (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Effective financial administration management depends not only on the accuracy of numbers, but also on the completeness and orderliness of supporting documents. At PT Swabina Gatra, weaknesses in the documentation system-particularly the lack of consistent utilization of receipts-caused difficulties in the process of tracing transactions and verifying invoices. This activity aims to encourage increased awareness and discipline of staff in using receipts as part of the internal control mechanism. The implementation was carried out through a hands-on approach, including mapping the work procedures of the Billing Unit, designing a standardized receipt format, and implementing a structured document delivery and filing system. The consistent application of receipts has been proven to reduce the risk of information loss and recording errors, and support the establishment of a more orderly and transparent work environment. With organized documentation, the company has a strong foundation to ensure accountability and traceability of every financial activity.